Regulation of GABA(A) receptors by fragile X mental retardation protein - Liu, Baosong (e-Century Publishing Corporation, 2013)
Fragile X syndrome (FXS) is caused by the loss of fragile X mental retardation protein (FMRP). The deficiency of GABA(A) receptors (GABA(A)Rs) is implicated in FXS. However, the underlying mechanisms remain unclear. To investigate the effect of FMRP on GABA(A)Rs, we transfected FMRP cDNAs in rat cortical neurons. We measured the protein expression of GABA(A)Rs and phosphatase PTEN, and recorded GABA(A)R-mediated whole-cell currents in the transfected neurons. We show that the transfection of FMRP cDNAs causes increased protein expression of GABA(A)Rs in cortical neurons, but GABA(A)R-mediated whole-cell currents are not potentiated by FMRP transfection. These results suggest the possibility that intracellular signaling antagonizing GABA(A)R activity may play a role in inhibiting GABA(A)R function in FMRP-transfected neurons. We further show that FMRP transfection results in an enhanced protein expression of PTEN, which contributes to the inhibition of GABA(A)R function in FMRP-transfected neurons. These results indicate that GABA(A)Rs are regulated by FMRP through both an up-regulation of GABA(A)R expression and a PTEN enhancement-induced inhibition of GABA(A)R function, suggesting that an abnormal regulation of GABA(A)R and PTEN by the loss of FMRP underlies the pathogenesis of FXS.